Improve Learning Outcomes passing in the Game of Football Through the Learning Model problem Based Learning (PBL) in Class XI Students of SMA Negeri 6 Ambon - Bahta, Ulfa Tamara; Hasbullah, B.; Hattu, M. (International Journal of Education, Information Technology, and Others, 2024)
The purpose of this research is to find out whether the learning model is implementedproblem based learning can improve passing learning outcomes in class XI students at SMA Negeri 6 Ambon. The research method used in this research is classroom action research. The subjects of this research were 25 class XI students of SMA Negeri 6 Ambon. After processing and analyzing the data, the results of cycle I were obtained based on the cycle I learning results table above, there were 12 students who had completed it or 48%. Meanwhile, 13 students have not yet completed or 52%. Cycle II based on the recapitulation table of student learning completion in cycle II above, there were 25 students who completed or (100%) and there were no students who did not complete or (0%). From the results of data analysis and calculations, it can be concluded that the application of the learning modelproblem based learning in learning football can improve passing learning outcomes in class XI students at SMA Negeri 6 Ambon